Physiological and biochemical features of fig cultivars (Ficus carica L.) from the collection of the Nikita Botanical Gardens - E. L. Shishkina; E. V. Dunaevskaya; R. A. Pilkevich; N. Yu. Marchuk (Труды по прикладной ботанике, генетике и селекции)
Background. Identification of promising fig cultivars (Ficus carica L.) with high content of bioactive compounds in fruits and increased adaptability to moisture deficiency is important for breeding and fruit growing in arid regions.Methods. The chemical analysis of fruits was performed using conventional methods. The content of essential elements was measured on a Kvant 2MT atomic absorption spectrophotometer. Drought resistance was assessed using the method of determining the water-holding capacity and resistance to dehydration in the leaves of fruit crops.Results. Fruits of cv. ‘Muason’ demonstrated the highest dry matter content (26.60 ± 1.30%), total phenolic compounds (169.0±26.0 mg%), sugars (mono: 15.03 ± 1.25%, and total: 17.46 ± 0.56%), water-soluble pectin (1.17%), total pectin substances (1.99%), and K (13565 ± 805 mg/kg); fruits of cv. ‘Pomoriysky’ had the maximum content of Ca (532 ± 65 mg/kg), Mg (982 ± 121 mg/kg), and Mn (1.98 ± 0.182 mg/kg); ‘Sabrutsiya Rozovaya’ excelled in the content of ascorbic acid (17.32 ± 0.78 mg%), Fe (15.413 ± 1.989 mg/kg), Zn (10.688 ± 1.338 mg/kg), and Cu (1.435 ± 0.132 mg/kg). ‘Sabrutsiya Rozovaya’ showed high drought resistance, ‘Pomoriysky’ had a medium degree of resistance, while ‘Muason’ demonstrated low water regime values. The loss of 15–20% of moisture by the leaves is critical: dehydration exceeding this limit leads to the impossibility of restoring satisfactory turgor. Conclusion. Fruits of the studied fig cultivars belong to the group of products with high K and Mg content, and satisfactory content of Fe, Zn and Mn. ‘Sabrutsiya Rozovaya’, a potentially adaptable cultivar with resistance to hydrothermal stress, was identified for its increased water-retaining capacities and high reparative ability of leaf tissues. It is recommended for use in the breeding for drought resistance and for establishment of large-scale plantations in arid regions.